Serotype-specific correlates of protection for pneumococcal carriage: an analysis of immunity in 19 countries - Voysey, M; Fanshawe, T; Kelly, D; O'Brien, K; Kandasamy, R; Shrestha, S; Thorson, S; Hinds, J; Pollard, A (Oxford University Press, 2017)
Pneumococcal conjugate vaccines (PCVs) provide direct protection against disease in those vaccinated, and interrupt transmission through the prevention of nasopharyngeal carriage.We analysed immunogenicity data from 5224 infants who received PCV in prime-boost schedules. We defined any increase in antibody between the one-month post-priming visit and the booster dose as an indication of nasopharyngeal carriage ('seroincidence'). We calculated antibody concentrations using receiver-operator characteristic curves, and used generalised additive models to compute their protective efficacy against seroincidence. To support seroincidence as a marker of carriage, we compared seroincidence in a randomised immunogenicity trial in Nepal with the serotype-specific prevalence of carriage in the same community.In Nepalese infants, seroincidence of carriage closely correlated with serotype-specific carriage prevalence in the community. In the larger data set, antibody concentrations associated with seroincidence were lowest for serotypes 6B and 23F (0.50 µg/mL and 0.63 µg/mL respectively), and highest for serotypes 19F and 14 (2.54 µg/mL and 2.48 µg/mL respectively). The protective efficacy of antibody at these levels was 62% and 74% for serotypes 6B and 23F, and 87% and 84% for serotypes 19F and 14. Protective correlates were on average 2.15 times higher in low/lower middle income countries than in high/upper middle income countries (GMR 2.15, 95%CI 1.46-3.17, p=0.0024).Antibody concentrations associated with protection vary between serotypes. Higher antibody concentrations are required for protection in low-income countries. These findings are important for global vaccination policy, to interrupt transmission by protecting against carriage.